Can sudden sensorineural hearing loss predict stroke? A long-term study - Rodríguez-Valiente, Antonio; García-Sebastián, Cristina; García-Berrocal, José Ramón (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2020)
Introduction: Previous studies suggest that vascular diseases as stroke may occur in a high percentage of patients with idiopathic sudden sensorineural hearing loss. Objective: To report the relationship between SHL and stroke in order to be used as an early risk marker for stroke. Material and Methods: We carried out a long-term followup study of all idiopathic sudden sensorineural hearing loss patients admitted to a tertiary referral center, between January 1994 and December 2006. All the patients were followed up on an outpatient basis until March 2019. Work-up study included history, otomicroscopy, audiometry, tympanometry, laboratory, and the development of vascular diseases, and specifically stroke. Stroke and transient ischemic attack were defined according to the WHO criteria. Results: A total of 214 patients were diagnosed with idiopathic sudden hearing loss, and 64 patients were assessed for stroke. Stroke after idiopathic sudden hearing loss was reported in 7 patients. Lacunar stroke or small-artery occlusion was the most frequent form of stroke presentation. The majority of cases occurred within the first 10 years after idiopathic sudden hearing loss, although two cases occurred at 14 and 20 years. Conclusion: There seems to be a relationship between SHL and stroke, especially in patients with cardiovascular risk factors. We recommend a longer follow-up in such a patients since stroke may develop several years after the onset of the hearing loss episode.